BpV(pic) confers neuroprotection by inhibiting M1 microglial polarization and MCP-1 expression in rat traumatic brain injury. (August 2019) - Liu, Rui; Liao, Xin-Yu; Tang, Jun-Chun; Pan, Meng-Xian; Chen, Song-Feng; Lu, Pei-Xin; Lu, Long J; Zhang, Zhi-Feng; Zou, Ying-Ying; Bu, Li-Hong; Qin, Xing-Ping; Wan, Qi
Highlights: BpV(pic) plays a neuroprotective effect in rat traumatic brain injury.BpV(pic) inhibits TBI-induced M1 microglial polarization via AKT/p65 signaling pathway. BpV(pic) alleviates the increase of microglia in TBI lesion region. Abstract: Traumatic brain injury (TBI) is a major cause of motor and cognitive impairment in young adults. It is associated with high mortality rates and very few effective treatment options. Bisperoxovanadium (pyridine-2-carboxyl) [bpV(pic)] is an commercially available inhibitor of Phosphatase and tensin homolog (PTEN). Previous studies have shown that bpV(pic) has protective effects in central nervous system. However, the role of bpV(pic) in TBI is unclear. In this study we aimed to investigate the neuroprotective role of bpV(pic) in rat TBI model. We found that injection of bpV(pic) significantly reduces brain edema and neurological dysfunction after TBI and this is mediated by AKT pathway. TBI is known to promote the M1 pro-inflammatory phenotype of microglial polarization and this effect is inhibited by bpV(pic) treatment which, instead promotes M2 microglial polarization in vivo and in vitro. We also found evidence of bpV(pic)-regulated neuroinflammation mediated by AKT activation and NF-κB p65 inhibition. BpV(pic) treatment also suppressed microglia in the peri-TBI region. MCP-1 is known to recruit monocytes and macrophages to promote inflammation, we show that bpV(pic) can inhibit TBI-induced up-regulation of MCP-1 via the AKT/NF-κB p65 signaling pathway. Taken together, our findings demonstrate that bpV(pic) plays a neuroprotective role in rat TBI, which may be achieved by inhibiting M1 microglia polarization and MCP-1 expression by modulating AKT/NF-κB p65 signaling pathway.